A escrita literária na confluência de linguagens estéticas : relações entre palavra e imagem em Sérgio Sant'Anna - Tedesco, Patrick (2013)
This study is the result of an interdisciplinary critical comparatist investigation of three narratives from Brazilian writer Sérgio Sant Anna - the short stories Cenários (1982) and A mulher nua (2003), as well as the fiction text O livro de Praga: narrativas de amor e arte (2011). The line of investigation is the study of the relation between word and image, focusing on the relation between Literature and Visual Arts, which can be both identified in Sant´Anna s texts. Concepts and theoretical contributions not only from the field of literary studies were applied, but also from the intertextuality and semiotic theories, which deal with the relation between verbal and imagetic textualities. The results corroborate the understanding that Sant´Anna`s writing has the characteristic of being self-referring, intersemiotic and problematizing of the literary production activity.